Analisis Perawatan Mesin dengan Menggunakan Metode Reability Centered Maintenance dan Fuzzy Fuzzy Failure Mode and Effect Analysis - Wahyuridho Dwi Ramadhan; Asep Endih Nurhidayat (Publikasi Indonesia, 2022)
In the company there is a problem, namely the high number of downtime that occurs in the SEYI SN-110 Ton press machine at PT. Padma Soode Indonesia. The purpose of this research is to find out the right maintenance action on the system that has been selected using the RCM Reability Centered Maintenance method, to find out which components are prioritized (critical) using Fuzzy FMEA (Failure Mode and Effect Analysis), and provide policy proposals in the form of SOPs. Both methods are types of quantitative methods. The results of data collection are the number of damage to the engine inside that is as much as 40 times in 1 year with a critical percentage of 77%. This has a very big impact on the company where in 1 day the production time / shift is 8 hours, with the downtime level reaching 8 hours which can be said in 1 day there is no production. From the results of data processing using RCM to overcome downtime, namely by doing machine maintenance for 47 days so that there is no more severe downtime later. 47 days to maintain the machine starting from cleaning, replacing components whose economic value is already low and looking at the level of the machine's ability to operate, the results of the research that obtained high critical level components are engine parts with a defuzzication rate of 155. The SOP for machine maintenance uses machine maintenance time from RCM worksheet results.